Electrochemical‐In‐Situ‐Oxidative Sulfonylation of Phenols with Sulfinic Acids as an Access to Sulfonylated Hydroquinones. Issue 14 (14th June 2021) - Sun, Xue; Zhang, Fanjun; Yan, Kelu; Feng, Wenfeng; Sun, Xuejun; Yang, Jianjing; Wen, Jiangwei
Abstract: The electrochemical in‐situ oxidative sulfonylation of phenols with sulfinic acids access to sulfonylated hydroquinones has been developed. A series of sulfonylated hydroquinones were prepared under mild mediator‐, catalyst‐ and exogenous‐oxidant‐free conditions. Notably, such an electrochemical in‐situ‐oxidative synthetic strategy presented wide functional group tolerance and amenability to gram‐scale synthesis with 62–80% yields. Abstract :